THE USE OF STORY REENACTMENT TO IMPORVE STUDENTS’ SPEAKING SKILL - Fikris Raberti (English Education Department Slamet Riyadi University Surakarta, 2020)
Speaking is a basic life skill of students success in school and consequently through life. Without the ability to speak effectively, the students can not improve their speaking skill. Hence, the aims of the this research were to find out whether Story Reenacment can improved students speaking skill and to find out the class condition when Story Reenacment was implemented in teaching learning process at the Eleventh grade of MAN 1 Surakarta in the Academic Year of 2019/2020. This research was conducted at the Eleventh grade of MAN 1 Surakarta. The method of the study was classroom action research which was conducted from October until January 2020. The data was collected through test and non-test. In collecting data was used audio recording in pre-test, post-test 1, and post-test 2. Besides that to collect non-test was used observation, interview, documentation, and questionnaire. While, to analyze the data was used t-test. The results of the research showed that the implementation of Story Reenacment was successful to improve students speaking skill. The mean score increased from 49.77 in pre-test became 58.55 in post-test 1 until 72.55 in post-test 2. There were significant improvements of the students’ motivation and situation in teaching learning process. The teaching learning process using Story Reenactment was very interesting. The students more enjoyed in teaching learning English. It can be concluded that Story reenacment was appropriate to improve the students speaking skill in teaching and learning process. Moreover, The class condition was more enjoyable, enthusiast, and conducive during learning process. Key words: Speaking Skill; Story Reenacment; Classroom Action Research